“Een merkwaardig misverstand”: Postcolonial reflections on Hoepla - Schoenberger, Janna (Farol, 2025)
This article is based on a Dutch television event from the 1960s. In a dark humor program, the first nude woman was shown on Dutch television; however, its impact overshadowed the subsequent event, the demonstration of a reality made invisible on Dutch soil: the Moluccans residing in the country. The ignorance and unpreparedness of those involved in the interview, and the surreal nature of the living conditions of Indonesian immigrants after the violent process of Dutch colonization in Indonesia, are discussed. This "event" on the television program Hoepla is developed in the article from the perspective of Ludic Conceptualism, a terminology coined by Dr. Schoenberger and applied to the artistic trend strongly present in the Netherlands between the 1960s and 1970s.
Keywords: Indonesia; ludic; media; post-colonialism